Switching Rho GTPase activation into effective antibacterial defenses requires the caspase-1/IL-1beta signaling axis - Boyer, Laurent (Small GTPases, 2015)
The monitoring of the activation state of Rho GTPases has emerged as a potent innate immune mechanism for detecting pathogens. In the March issue of PLOS Pathogens, we show that the activation of Rho GTPases by the CNF1 toxin during E. coli-triggered bacteremia leads to a GR1(+)cell-mediated efficient bacterial clearing and improves host survival. Host alarm requires the Caspase-1/IL-1beta signaling axis. Furthermore, we discover that pathogenic bacteria have the capacity to block immune responses via the expression of the α-hemolysin pore-forming toxin. In this commentary, we will comment on these findings and highlight the questions raised by this example of attack-defense mechanisms used alternatively by the pathogen and the host during blood infection.